ROMANIAN CHOIRS FROM SEBEŞ-ALBA - Dragoş Ioan ŞUŞMAN (Studia Universitatis Babeş-Bolyai. Musica)
The present study provides an overview of the musical life of the Romanians in Sebeş, with a deeper insight into the choral work performed by them in the late 19th century and the first half of the 20th. The existence of the four choir groups presented here is related to the names of institutions or associations under the patronage of which they functioned: the Sebeş Orthodox Parish, the Astra Division of Sebeş and the “Sfântul Gheorghe” Association. The material is compiled, to a large extent, from documents belonging to the funds of Astra, the Sebeş division and the Orthodox Parish of Sebeş preserved in the Romanian National Archives, Alba County Branch.